Epigenomic dysregulation in the bone marrow mesenchymal stem cells of acquired aplastic anemia patients: An in silico and in vitro study - Pragati Saxena; Aishwarya Upadhyaya; Bhuvnesh Rai; Jyotika Srivastava; Ruchi Gupta; Sanjeev Yadav; Chandra Prakash Chaturvedi (Molecular Biology Reports, 2026)

Unveiling the contemporary genetic diversity and population demography of the critically endangered northern river terrapin (Batagur baska) in the sundarbans - Ajit Kumar; Anand Sharma; Naveen Negi; Ruchi Badola; Syed Ainul Hussain; Sandeep Kumar Gupta (Molecular Biology Reports, 2026)

Scientific evidence validating spiritual beliefs for controlling pathogenic microbes in the Ganga river - Sanjay Dwivedi; Ruchi Agnihotri; Vishnu Kumar; Seema Mishra; Ravi Kumar Tiwari; Dibyendu Adhikari; Pragya Sharma; Sarvesh Kumar; Tuhina Verma; Apoorv Gupta; Geetgovind Sinam; Vivek Pandey (Journal of Environmental Sciences, 2026)

Green synthesis of Carbopol-silver nanoparticles using Hibiscus rosasinensis and Cymbopogon citratus: A synergistic in vitro and in vivo approach for accelerated wound healing in Swiss albino mice - Shivam; Tinku Gupta; Reena Badhwar; Ruchi Singh (Biocatalysis and Agricultural Biotechnology, 2026)

Lowering arsenic threshold in water, soil and food products: an urgent need of 21st century for safeguarding the environment and human health - Sanjay Dwivedi; Seema Mishra; Apoorv Gupta; Ruchi Agnihotri; Pragya Sharma; Ravi Kumar Tiwari; Vishnu Kumar; Vinay Kumar (Environmental Sustainability, 2026)

Combating garlic white rot: evaluating the potency of biofumigants and indigenous Trichoderma strains against Sclerotium cepivorum - Shavnam; Narender Kumar Bharat; Meenu Gupta; Ruchi Sharma; Sonali Parwan (Indian Phytopathology, 2026)

Stubble Burning and Air Pollution in Delhi: Assessment of Mitigation Strategies - Manas Kumar Jha; Ruchi Gupta; Ashutosh Kainthola; Vaishali Sahu; Pranavi Mishra; Dilip Kumar Markandey; Shahbaz Alam (Anthropocene Science, 2025)

Sustainable bio-valorisation of water hyacinth for enhancing rural livelihood and achieving sustainable development goals - Apurba Koley; Nitu Gupta; Sandipan Banerjee; Arunkumar Patchaiyappan; Tapas Bagdi; Rai Dhar Ruchi; Sristi Debnath; Shibani Chaudhury; Annamalai Muthusamy; Amit Kumar Hazra; Srinivasan Balachandran (Bioresource Technology Reports, 2025)

Genetic diversity, spatial connectivity, and population structure of Asian silurid catfish Wallago attu (Bloch and Schneider, 1801) in the Ganga River System: insights from mitochondrial DNA analysis - Ajit Kumar; Naveen Negi; Neha Yadav; Ruchi Badola; Syed Ainul Hussain; Sandeep Kumar Gupta (Molecular Biology Reports, 2024)

Effective parallel evaluation of molecular design, expression and bioactivity of novel recombinant butyrylcholinesterase medical countermeasures - Joanne L. Allard; Miguel Aguirre; Ruchi Gupta; Sheena.M.H. Chua; Katherine A. Shields; Linda.H.L. Lua (Chemico-Biological Interactions, 2024)

Transcriptome Analysis for Gaining Insight into Gingerol Biosynthesis and MAPK-Dependent Hormonal Signaling Pathway Involved in Resistance Mechanism in Fusarium Wilt Tolerant Ginger (Zingiber officinale Rosc.) Produced Through In Vitro Mutagenesis and Selection - Pooja Sharma; Manisha Thakur; Shwet Kamal; Anjali Chauhan; Happy Dev; Ruchi Gupta (Journal of Plant Growth Regulation, 2024)

Prevalence and Predictors of Restless Legs Syndrome in Patients Having Chronic Obstructive Pulmonary Diseases: A Systematic Review and Meta-analysis - Sabbu Maharjan; Rohit Kumar; Niraj Kumar; Lokesh Kumar Saini; Ruchi Dua; Ravi Gupta (Sleep and Vigilance, 2024)

Time for sustainable marketing to build a green conscience in consumers: Evidence from a hybrid review - Mahima Yadav; Ruchi Gupta; Kiran Nair (Journal of Cleaner Production, 2024)

Recent green chemistry approaches for pyrimidine derivatives as a potential anti-cancer agent: An overview (2013–2023) - Kumari Kajal; Ruchi Shakya; Mohd Rashid; Vaibhav Nigam; Balak Das Kurmi; Ghanshyam Das Gupta; Preeti Patel (Sustainable Chemistry and Pharmacy, 2024)

Evaluation of biomedical waste generation in Himachal Pradesh before and during the Covid 19 pandemic - Ruchi Doad; Renu Gupta; Ritu Shitak (Science of The Total Environment, 2024)

A comprehensive review on spatial and temporal variation of arsenic contamination in Ghaghara basin and its relation to probable incremental life time cancer risk in the local population - Sanjay Dwivedi; Seema Mishra; Vishnu Kumar; Ruchi Agnihotri; Pragya Sharma; Ravi Kumar Tiwari; Apoorv Gupta; Ajay Pratap Singh; Sarvesh Kumar; Geetgovind Sinam (Journal of Trace Elements in Medicine and Biology, 2023)

Macroeconomic analysis of a new green hydrogen industry using Input-Output analysis: The case of Switzerland - Ruchi Gupta; Thomas M.M. Guibentif; Markus Friedl; David Parra; Martin Kumar Patel (Energy Policy, 2023)

Simultaneous monitoring and dietary risk assessment of 386 pesticides in market samples of black tea - Vandana Tripathy; Krishan Kumar Sharma; Ruchi Gupta; Rajbir Yadav; Suneeta Devi; Khushbu Sharma; Gitansh Singh; Shobhita Kalra; Akanksha Aggarwal; Kesar Tandekar; Ankita Verma; Suresh Walia (Food Chemistry, 2023)

A critical analysis of various post-harvest arsenic removal treatments of rice and their impact on public health due to nutrient loss - Apoorv Gupta; Ravi Kumar Tiwari; Ruchi Agnihotri; Kalpana Padalia; Seema Mishra; Sanjay Dwivedi (Environmental Monitoring and Assessment, 2023)

Maize: an underexploited golden cereal crop - Manisha Kaushal; Ruchi Sharma; Devina Vaidya; Anil Gupta; Harpreet Kaur Saini; Anupama Anand; Chahat Thakur; Aastha Verma; Manisha Thakur; Priyanka; Dileep KC (Cereal Research Communications, 2023)

Aquaporins Display a Diversity in their Substrates - Ruchi Sachdeva; Pragya Priyadarshini; Sakshi Gupta (The Journal of Membrane Biology, 2023)

An Analysis of M-protein in Plasma cell Dyscrasia Patients Identifies that IgG Lambda Subtype is More Commonly Associated with Normal Serum Free Light Chain (SFLC) Ratio - Manish K. Singh; Vinita Paswan; Sonal Dwivedi; Ruchi Gupta; Khaliqur Rahman; Dinesh Chandra; Sanjeev Yadav; Anshul Gupta; Rajesh Kashyap; Soniya Nityanand (Indian Journal of Clinical Biochemistry, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Dissipation kinetics and risk assessment of iprovalicarb + propineb fungicide in tomato under different agroclimates - Vandana Tripathy; Krishan Kumar Sharma; Thomas George; Chidanand Shiveshankar Patil; Yogesh Subhash Saindane; Soudamini Mohapatra; Lekha Siddamallaiah; Abdul Rashid Khan Pathan; Amit Kumar Yadav; Khushbu Sharma; Rajbir Yadav; Ruchi Gupta; et al. (Environmental Science and Pollution Research, 2021)

Identification of Factors Associated with Hematology-Oncology Fellow Academic Success and Career Choice - Ariela L. Marshall; Ruchi Gupta; Diane Grill; Susan Mann; Kimberly Freidline; Grzegorz Nowakowski; Carrie Thompson; Timothy Hobday (Journal of Cancer Education, 2019)

Drinking water quality problem in Haryana, India: prediction of human health risks, economic burden and assessment of possible intervention options - Ruchi Gupta; Anil Kumar Misra (Environment, Development and Sustainability, 2019)

Oral Delivery of Methylthioadenosine to the Brain Employing Solid Lipid Nanoparticles: Pharmacokinetic, Behavioral, and Histopathological Evidences - Pramod Kumar; Gajanand Sharma; Varun Gupta; Ramanpreet Kaur; Kanika Thakur; Ruchi Malik; Anil Kumar; Naveen Kaushal; Om Prakash Katare; Kaisar Raza (AAPS PharmSciTech, 2019)

Characterization of recombinant dihydrodipicolinate synthase from the bread wheat Triticum aestivum - Ruchi Gupta; Campbell J. Hogan; Matthew A. Perugini; Tatiana P. Soares da Costa (Planta, 2018)

Persistence, dissipation and consumer risk assessment of a combination formulation of flubendiamide and deltamethrin on cucumber - K.K. Sharma; V. Shashi Bhushan; Cherukuri Sreenivasa Rao; K. Narsimha Reddy; Hemanta Banerjee; Swagata Mandal; Balwinder Singh; R.S. Battu; Gagan Jyot; S.K. Sahoo; Soudamini Mohapatra; S. Lekha; et al. (Food Additives & Contaminants: Part A, 2018)

Physiological performance, secondary metabolite and expression profiling of genes associated with drought tolerance in Withania somnifera - Sanchita; Ruchi Singh; Anand Mishra; Sunita S. Dhawan; Pramod A. Shirke; Madan M. Gupta; Ashok Sharma (Protoplasma, 2015)

Prevalence of Vitamin D Deficiency in a Pediatric Hospital of Eastern India - Surupa Basu; Ruchi Gupta; Monjori Mitra; Apurba Ghosh (Indian Journal of Clinical Biochemistry, 2015)

In vivo Toxicity Assessment of Antimicrobial Peptides (AMPs LR14) Derived from Lactobacillus plantarum Strain LR/14 in Drosophila melanogaster - Ruchi Gupta; Surajit Sarkar; Sheela Srivastava (Probiotics and Antimicrobial Proteins, 2014)

Mild and highly efficient copper (II) sulfate catalyzed one pot synthesis of 2-aryl benzimidazole using atmospheric air as an oxidant and its antibacterial study - Raginee Jain; D. D. Agarwal; Pramod K. Sahu; D. Thava Selvam; Yogesh Sharma; Ruchi Gupta; Archana Prakash (Medicinal Chemistry Research, 2013)

Development, validation, and uncertainty measurement of multi-residue analysis of organochlorine and organophosphorus pesticides using pressurized liquid extraction and dispersive-SPE techniques - Doyeli Sanyal; Anita Rani; Samsul Alam; Seema Gujral; Ruchi Gupta (Environmental Monitoring and Assessment, 2011)

Optimization of Lipase Production from Aspergillus terreus by Response Surface Methodology and Its Potential for Synthesis of Partial Glycerides Under Solvent Free Conditions - Rekha Kaushik; Ruchi Gulati Marwah; Pritesh Gupta; Saurabh Saran; Luciano Saso; V. S. Parmar; R. K. Saxena (Indian Journal of Microbiology, 2010)

Fermentation waste of Aspergillus terreus: a potential copper biosorbent - Ruchi Gulati; R.K. Saxena; Rani Gupta (World Journal of Microbiology and Biotechnology, 2002)